Combined spinal-epidural anesthesia in a patient with spinal muscular atrophy type II undergoing a cesarean section: A case report - Krušić, Slavica; Nikolić, Branka; Maglić, Rastko (Vojnosanitetski pregled, 2021)
Introduction. Anesthetic management of a patient with spinal muscular atrophy type II, who underwent elective cesarean section with neuraxial anesthesia is presented in this case report. Case report. A 33-year old woman with first pregnancy and no previous birth, at 39 weeks gestational age was scheduled for a cesarean section due to placenta previa. She had a history of spinal muscular atrophy type II, that confined her to a wheelchair, and a surgical history that included corrective surgery for kyphoscoliosis. The patient had predictors for a difficult intubation (limited mouth opening and reduced neck extension) so the decision was made to attempt the needle-through-needle combined spinal-epidural technique for surgical anesthesia. Harrington rods and scar tissue complicated placement of the combined spinal-epidural anesthesia, however successful placement was achieved. Conclusion. Spinal muscular atrophy in pregnancy is rare and represents big challenge for an anesthesiologist due to respiratory dysfunction, anticipated difficult intubation, severe kyphoscoliosis and limitations of the use neuromuscular blocking agents. The potential risks need to be considered when administering anesthesia in patients with spinal muscular atrophy undergoing a cesarean section.